Salivary and serum concentrations of cortisol and testosterone at rest and in response to intense exercise in boys versus men - Adebero,T.; McKinlay, B. J.; Theocharidis, A.; Root, Z.; Josse, A. R.; Klentrou, P.; Falk, B. (Pediatric Exercise Science, 2020)
This study compared salivary and serum concentrations of testosterone and cortisol at rest and in response to intense multitaskexercise in boys and men. Early morning saliva and venous blood samples were obtained before and 15 minutes after exercisefrom 30 competitive swimmers (15 boys, age 14.3 [1.9] y; 15 men, age 21.7 [3.1] y). Exercise included a swim-bench maximalstrength task and an all-out 200-m swim, followed by a high-intensity interval swimming protocol (5×100 m, 5×50 m, and 5×25 m). At baseline, fasting testosterone (but not cortisol) concentration was higher in men than boys in serum and saliva (P<.05).Salivary and serum cortisol increased postexercise, with a greater increase in men compared with boys (men: 226% and 242%; boys: 78% and 64%, respectively; group by time interaction,P<.05). Testosterone was reduced postexercise in serum but not insaliva (men:-14.7% and 0.1%; boys:-33.9% and-4.5%, respectively,fluid by time interaction,P<.01). Serum and salivarycortisol (but not testosterone), preexercise and postexercise values were strongly correlated in both men and boys (r=.79 and .82,respectively;P<.01). In summary, early morning high-intensity exercise results in a decrease in testosterone in serum, but notsaliva, and an increase in cortisol irrespective of thefluid used, in both boys and men. When examining immediate postexercisechanges, the lack of correlation in testosterone between saliva and serum suggests that saliva may not be an appropriatefluid toexamine changes in testosterone. The high correlation observed between serum and saliva for cortisol indicates that, in both boysand men, saliva may be used to monitor the immediate cortisol response to exercise.